Getting food policy on the Mayoral table: a comparison of two election cycles in New York and London. Issue 4 (April 2015) - Freudenberg, N.; Atkinson, S.
Abstract Cities and Mayors are increasingly being recognized as important in shaping social policy and improving social well-being. And municipal food policies are increasingly important as a tool to reduce food insecurity and prevent diet-related chronic diseases. Thus city governments have a unique ability to improve local food environments. To realize this potential for improving urban food environments, nutrition advocates will need to find innovative approaches for influencing municipal food policy. This paper examines Mayoral elections as a vehicle to advance food policy. To explore this strategy, Mayoral elections in two cities, New York City (NYC) and London, during two recent cycles were compared. To gather evidence multiple sources were used including campaign documents, media and opinion polls as well as the authors' own observations as food policy observers and participants in the two cities. Mayoral governance differs between NYC and London, with the Mayor in NYC having greater powers of management and administration, whilst the London Mayor has a more strategic role and may need to also use 'influence'. Food policy and related issues did not feature strongly in the first election cycles in either city. However by the 2012 and 2013 elections food issues were definitely 'on the table' and featured in main candidates' campaign literature. These latter elections also saw the importance of food advocates coming together to form common alliances and place food issues higher on the municipal agenda. In this way, food policy has become part of the election dialogue in both cities and candidates are expected to consider food policy issues. This analysis leads to make observations which could guide advocates as to how to use Mayoral elections to raise policy objectives for the benefit of public health.